Tashkent, Bukhara and Khorezm republics, epidemics, and fight against them - Karomov G’. Kh (Universitas Muhammadiyah Sidoarjo, 2019)
The article concludes that the outbreak of epidemics is a major factor in the poor living conditions of the population. In human history, epidemics are a real catastrophe for the population, which is based on the fact that wars, natural conditions, coastal and famine-stricken factors are its companions. History tells about the